Mechanisms underlying immobilization‐induced muscle pain in rats. Issue 5 (8th March 2020) - Oga, Satoshi; Goto, Kyo; Sakamoto, Junya; Honda, Yuichiro; Sasaki, Ryo; Ishikawa, Kumiko; Kataoka, Hideki; Nakano, Jiro; Origuchi, Tomoki; Okita, Minoru
Abstract: Introduction: We investigated the mechanisms underlying immobilization‐induced muscle pain in rats. Methods: In rat skeletal muscle, pressure pain threshold (PPT) of the gastrocnemius muscle was measured, and nerve growth factor (NGF) level, peripheral nerve fiber density, macrophage number, and interleukin‐1β (IL‐1β) mRNA expression were examined. An NGF receptor inhibitor was injected intramuscularly to assess the relationship between PPT and NGF levels. Results: Immobilization resulted in a decrease in PPT and increases in NGF level, C‐fiber density, M1 macrophage number, and IL‐1β mRNA expression. Injection of NGF receptor inhibitor reversed the decrease in PPT. Discussion: NGF upregulation may be a major contributor to immobilization‐induced muscle pain. The increases in C‐fiber density, M1 macrophage number, and IL‐1β mRNA expression may be related to immobilization‐induced muscle pain.